EFFECT OF BRAND TRUST AND FOOD SAFETY ON PURCHASING DECISION OF PACKAGING PRODUCTS: (Studies on Supermarket in the City of Medan) - Safitri, Gadis Ayu; Lumbanraja, Posma; Marpaung, Nicholas (Transpublika Publisher, 2023)
well as the effect of product safety on purchasing decisions, and the effect of brand trust and product safety together on purchasing decision of Le Minerale bottle product in Supermarket in the City of Medan. This research employed a quantitative technique with an associative approach. The population involved was Le Minerale consumers, namely people who had consumed Le Minerale products, both men and women. The sampling method was done by purposive sampling. The results showed that the brand trust variable partially showed F-statistic> F-table (7,789> 1,996) with sig. as big as (0,000), which means that the brand trust variable has a positive and significant effect on purchasing decisions. The product safety variable partially shows the F-statistic (4.571)> t-table (1.996) with sig. as big as (0,000), which means that the product safety variable has a positive and significant effect. Against purchasing decisions. Based on the simultaneous test (F-Test), it can be seen that the F-statistic (258,254) and F-table (3,09) with sig. (0,000), which means that the variables of brand trust and product safety together have a positive and significant effect on purchasing decisions. The analysis of determination is seen from the R Square value of 0.842, which means that the decision to purchase Le Minerale packaged products at supermarkets in Medan City can be fulfilled by brand trust and product safety by 84.2%. While the remaining 15.8% can be explained by other factors which were not examined in this study.